Penguasaan Hak atas Tanah Bagi Warga Negara Asing Di Indonesia - Sufrianto Y. Hanapi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2017)
This study discusses the status of land ownership for foreigners in Indonesia. This research is a qualitative research using an empirical juridical approach. Research data obtained from interviews and literature studies. The results showed that the status of ownership of foreigners of land in the province of Indonesia is the usufructuary rights as stipulated in Law Number 5 of 1960 concerning Basic Agrarian Regulations and Government Regulation Number 40 of 1996 concerning the right to use is not granted ownership rights. The process of granting land rights for foreigners in Indonesia is in accordance with the laws and regulations set out in Law Number 5 of 1960 concerning Basic Rules of Agrarian Principles and Government Regulation Number 40 of 1996.